Indium(III) Triflate‐Catalyzed Glycosylation through an Ambient Activation of Glycosyl Fluoride. Issue 1 (7th December 2018) - Sim, Jaehoon; Kim, Seok‐Ho; Hur, Joonseong; Lim, Changjin; Kim, Hyun Su; Suh, Young‐Ger
Abstract: A highly efficient catalytic glycosylation using glycosyl fluoride in the presence of a mild and non‐toxic Lewis acid, indium(III) triflate, was achieved. The facile and convenient glycosylation procedure does not require pre‐activation steps, pre‐distillation, or cumbersome work‐up process, and it was compatible with a broad range of alcohol acceptors under ambient conditions. Furthermore, the stereoselective C‐glycosylation smoothly proceeded under the same conditions. Abstract : A highly efficient catalytic glycosylation using bench‐stable glycosyl fluoride in the presence of a mild and non‐toxic Lewis acid, indium(III) triflate, was described. In addition, the stereoselective C‐glycosylation proceeded under the same conditions.